In dark places remembering the holocaust - Rosenblatt, Dev; Mindess, Anna (New York : Phoenix Films, 1978)
Backup available in VHS 1/2 in.
Focuses on survivors of the Nazi prosecution and explores how they and their children cope today with the memory of the past
Keywords: Holocaust, Jewish (1939 -- 1945) -- Psychological aspects; Jews -- Psychology